Economy, Finance and Business in Southeastern and Central Europe Proceedings of the 8th International Conference on the Economies of the Balkan and Eastern European Countries in the Changing World (EBEEC) in Split, Croatia, 2016 (Springer Proceedings in Business and Economics,, 2018)
This volume comprises papers presented at the 8th international conference "The Economies of the Balkan and Eastern European Countries in the Changing World" (EBEEC) held in Split, Croatia in 2016. The papers cover a wide range of current issues relevant for the whole of Eastern Europe, such as European integration, economic growth, labour markets, education and tourism. Written by experienced researchers in the field of economic challenges for Eastern Europe, the papers not only analyse recent problems, but also offer policies to resolve them. Furthermore, they offer insights into the theoretical and empirical foundations of the economic processes described. The proceedings of the conference appeals to all those interested in the further economic development of the Balkan and Eastern European countries.